Demography of Cholanaickan, the Cave-men of Kerala – India - Bhanu, B. A.; Saheb, S. Yaseen (Anthropological Review, 1985)
Cholanaickans, a tribe of hunters-gatherers from Kerala State in India were investigated from the demographic aspect. On the basis of data from many years the dynamics of changes of the group structure was presented. Special attention was devoted to the mating system and reproduction.